Biopolymer based microneedles patch by laser technology for biomedical applications - Silvestre, Sara Isabel Laiginha (2018)
One of the most important issues in creating new drug delivery methods is improving drug permeation into the skin. Therefore, many techniques have been proposed, such as oral administration, intradermal vaccines, transdermal patches, among others, but all of them present several limitations. In the past few years, a new effective, innovative and safe drug delivery system was proposed. This technology is named as microneedles (MNs) and it is a hybrid combination of hypodermic injections and transdermal drug delivery systems, which consists in micro-scale needles that can pierce the skin by a simple, minimally invasive and painless route, enabling to transport drugs and macromolecules into the human body. This dissertation reports the development of a biopolymer-based microneedle patch, using biodegradable and biocompatible polymers, polylactic acid (PLA) and poly(hydroxybutyrate-co-hydroxyvalerate) (P(HB-co-HV)), through a low-cost and maskless laser technology. The laser technology was used to engrave specific patterns on a substrate that served as mold for the MNs production. The best results were obtained with a laser power of 30 W at 0.15 m/s, with the spiral model as pattern. The respective MNs had a length of 0.69 mm and a diameter of 0.33 mm, ideal for painless penetration of skin. Moreover, P(HB-co-HV) demonstrated a higher mechanical stability than commercial PLA, confirming its promising use as MNs biomaterial.